GASTROPOD MOLLUSKS FROM THE HAUTERIVIAN OF ULYANOVSK (VOLGA REGION): 2. GENERA KHETELLA BEISEL, 1977 AND CRETADMETE GEN. NOV - Blagovetshenskiy I.V.; Shumilkin I.A. (My University, 2006)
The diagnosis of the genus Khetella Beisel, 1977 is emended, and a new genus, Cretadmete, is described. Two new species belonging to these genera, K. trautscholdi and C. neglecta, are established from the Upper Hauterivian of Ulyanovsk (Volga Region). © Pleiades Publishing, Inc. 2006.
Keywords: GASTROPODS; ULYANOVSK; UPPER HAUTERIVIAN; VOLGA REGION; Hauterivian; Mesozoic::Cretaceous::Lower::Hauterivian; Мезозой::Меловая::Нижний::Готеривский